The Research of Chinese Immigrants and Crime - Zhang, Zihao; Wu, Zun; Sun, Yuwei; Yang, Lexin (International Journal of Social Sciences and Public Administration, 2025)
This study delves into the historical background of Chinese immigrants in the United States, crime issues, and the impact of socioeconomic factors on Chinese criminal behavior. The article first provides an overview of American immigration and the history of Chinese immigration, then analyzes the general situation of crime problems in the 1850s, with a particular focus on Chinese criminal activities. In the literature review section, this paper thoroughly examines the scale of Chinese criminal activity, crimes targeting Chinese individuals, motives behind these crimes, and the social impacts they bring. Finally, through detailed factual statements, the article elaborates on the rise of Chinese labor migration, post-migration social integration, social discrimination and exclusion, and how these factors contribute to the emergence of criminal behavior.